MAKSIMALKAN MANFAAT PROGRAM PEMBINAAN UNTUK LANSIA DI LEMBAGA PEMASYARAKATAN - Azuri, Thavarel; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This article aims to investigate ways to maximize the benefits of coaching programs aimed specifically at older adults in correctional facilities. Incarcerated older adults often face complex physical and mental health challenges, as well as social isolation. They require special attention and well-designed coaching programs to improve their quality of life. This article will discuss the importance of coaching programs for the elderly within correctional institutions, detail the elements needed to design an effective program, identify some of the challenges that may be faced in its implementation, as well as present some successful case studies as inspiration for developing better approaches to providing support to incarcerated elderly. The article also highlights the importance of social interventions, psychological support, access to adequate healthcare, and social activities in improving the quality of life of older detainees. Keywords: Intervention; Psychological; Elderly; Correctional Institution; Human Rights